KNOWLEDGE MANAGEMENT MATURITY AT DANA PENSIUN TELKOM - Khasin Arsyad, Zimam
Dana Pensiun Telkom (Dapen Telkom) is a company managing and providing pension funds to employees of PT. Telekomunikasi Indonesia. Today, Dapen Telkom is experiencing problems due to the failure of knowledge management in the company. This causes the performance of the company to experience fluctuations in the last five years, due to the occurrence of information gaps within the organization. The value of knowledge management proves it in the Superior Performance Assessment Criteria (KPKU), which is still relatively low and has not shown signs to the company's vision. Besides, the company is currently at risk of losing knowledge assets, because 31% of top management employees will retire. So that knowledge management is very critical for Dapen Telkom to do repairs. The need for measuring the maturity level of knowledge management that has occurred in the company so that the writer can provide advice to develop knowledge management. In the author's research method uses a qualitative and quantitative approach. The qualitative approach uses in-depth interviews about knowledge management within the company with resource persons from three leaders of human resources and three ordinary employees. The quantitative approach uses a survey of 64 respondents using seven categories from the APO Framework. Using these two methods, the author will get things that affect the inhibition of knowledge management and the maturity level of knowledge management. From the results of the analysis that has been done, knowledge management is at level three, namely: expansion. Where companies have carried out knowledge management functions, but only occur in several departments. Knowledge management has not been massive in all departments within the business. After the author makes a root cause of the problem that arises, then suggests that the company takes the initiative towards the knowledge management program. Namely through; leadership, KM team, knowledge cafe, project/training lesson learned, and digital learning.